CORRELATION BETWEEN SIBLING RIVALRY AND ACHIEVEMENT MOTIVATION IN TWINS - Jelita Widuri Yati; Frieda M. Mangunsong (Universitas Gunadarma, 2008)
The aim of this study is to know the correlation between sibling rivalry and achievement motivation in twins. This is an quantitative approach research with 32 twin boys and girls. The result shows that there is no correlation between sibling rivalry and achievement motivation in twins. Theory said that the twins will make an effort as much as the other twin to have the same academic and non academic achivement. It means the other twin tries to get higher achievement or lower achievement to the other twin that has lower capability.Key words: sibling rivalry, achievement motivations, the twins